STRATEGI PENGELOLAAN KELAS YANG EFEKTIF DALAM MENUMBUHKAN SIKAP DISIPLIN SISWA - Yantoro Yantoro (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The purpose of this study is to describe the strategies of effective classroom teachers in growing student discipline. This study used a qualitative phenomenological approach with the subject of the study being three high school teachers of SDN 211 / IX Mendalo Darat. Data is collected through observation and interviews and analyzed by classifying data, reducing data, presenting and drawing conclusions. The results showed an effective classroom management strategy undertaken by the teacher in fostering student disciplinary attitudes reflected in optimizing classroom management, seating arrangements that are hydrogen, playing sound intonation during learning, and student attendance in class on time. The research concludes that students' disciplinary attitudes can be grown by the teacher's strategy in effective classroom management.